2017
DOI: 10.1111/acer.13514
|View full text |Cite
|
Sign up to set email alerts
|

Variation in SWI/SNF Chromatin Remodeling Complex Proteins is Associated with Alcohol Dependence and Antisocial Behavior in Human Populations

Abstract: Background Testing for direct gene/SNP replication of association across studies may not capture the true importance of a candidate locus; rather, we suggest that relevant replication across studies may be found at the level of a biological process. We previously observed that variation in two members of the SWI/SNF chromatin remodeling complex is associated with alcohol dependence (AD) in the Irish Affected Sib Pair Study for Alcohol Dependence. Here, we tested for association with alcohol-related outcomes us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 58 publications
(70 reference statements)
0
11
0
Order By: Relevance
“…Alcohol has also been demonstrated to establish long-lasting changes in BAF CRC function. Recently Mathies et al (2017) identified several SNP clusters within BAF-genes that correlate with alcohol use disorder in humans, including Baf47 , Baf60a , and Crest [ 141 ]. Lastly, ethanol exposure during neuronal development induces expression of Baf53b , Baf57 , Baf60 , Baf200 , and Crest [ 142 ].…”
Section: Epigenetics In Substance Use Disordersmentioning
confidence: 99%
“…Alcohol has also been demonstrated to establish long-lasting changes in BAF CRC function. Recently Mathies et al (2017) identified several SNP clusters within BAF-genes that correlate with alcohol use disorder in humans, including Baf47 , Baf60a , and Crest [ 141 ]. Lastly, ethanol exposure during neuronal development induces expression of Baf53b , Baf57 , Baf60 , Baf200 , and Crest [ 142 ].…”
Section: Epigenetics In Substance Use Disordersmentioning
confidence: 99%
“…In worms, most SWI/SNF complex members were involved in regulating acute ethanol response behaviors, but different SWI/SNF complexes affected different behaviors: BAF subunits were required for normal initial sensitivity to ethanol, while PBAF subunits were required for acute functional tolerance to ethanol [ 10 ]. We found that allelic variation in several SWI/SNF complex members was associated with alcohol dependence in different adult human populations [ 10 , 14 ]. Allelic variation in different SWI/SNF complex members was also associated with antisocial behavior in adolescents, a phenotype that is strongly predictive of future alcohol use problems [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that allelic variation in several SWI/SNF complex members was associated with alcohol dependence in different adult human populations [ 10 , 14 ]. Allelic variation in different SWI/SNF complex members was also associated with antisocial behavior in adolescents, a phenotype that is strongly predictive of future alcohol use problems [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in the human BCL7C gene are associated with the Sézary syndrome, which is a leukemic form of cutaneous T-cell lymphoma [191]. BCL7C (together with several other genes encoding subunits of the SWI/SNF complex, such as ACTB , ARID2 , BCL11A , BCL11B , BCL7B , BRD7 , DPF2 , DPF3 , SMARCB1 , SMARCD1 , and SS18L1 ) was also linked to the development of alcoholism and alcohol-related problems [192].…”
Section: Resultsmentioning
confidence: 99%